1992
DOI: 10.1111/j.1547-5069.1992.tb00733.x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Empathy: A Conceptual Fit for Nursing Practice?

Abstract: After three decades, the efficacy of empathy in the clinical setting remains undocumented. Recently, concerns have been raised that the concept may be inappropriate and even harmful to the nurse-patient relationship. An analysis of the concept indicates that empathy consists of moral, emotive, cognitive and behavioral components. By tracing the integration of this concept into nursing, we suggest that empathy was uncritically adopted from psychology and is actually a poor fit for the clinical reality of nursin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
221
0
13

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(237 citation statements)
references
References 63 publications
3
221
0
13
Order By: Relevance
“…18 There is evidence to support the claim that empathy increases motivation to perform pro-social and altruistic acts so overlapping with notions of compassion. 38,39 Feminist care ethics maintains that moral thought and action require both reasons and emotions as well as attention to the needs of particular others [40][41][42] From a care ethics perspective, the practice of caring is integral to the moral life and empathy is an important element of caring.…”
Section: Moral Empathymentioning
confidence: 81%
See 2 more Smart Citations
“…18 There is evidence to support the claim that empathy increases motivation to perform pro-social and altruistic acts so overlapping with notions of compassion. 38,39 Feminist care ethics maintains that moral thought and action require both reasons and emotions as well as attention to the needs of particular others [40][41][42] From a care ethics perspective, the practice of caring is integral to the moral life and empathy is an important element of caring.…”
Section: Moral Empathymentioning
confidence: 81%
“…18 This cognitive requirement differentiates empathy from sympathy and compassion. Cognitive empathy has been described as 'detached concern' or the ability of one individual to understand the experiences of another without evoking a personal emotional response.…”
Section: Cognitive Empathymentioning
confidence: 99%
See 1 more Smart Citation
“…22 From a broad perspective, empathy becomes a unique kind of understanding through which we experience what it is like to be another person:…”
Section: Appropriate Empathy: a Broad View That Can Humanise Clinicalmentioning
confidence: 99%
“…It has been suggested that it is possible to learn the cognitive components of empathy even in the absence of the affective component [17]. Medical practice is intense and often highly pressured.…”
Section: Discussionmentioning
confidence: 99%